Na podbój Imperium i świata. Brytyjki jako prekursorki kultury podróży i turyzmu - Łukowska, Maria (Imperium Brytyjskie: Rozważania interdyscyplinarne, 2019)
British women were the first of all other nationalities to travel around the world. Among the reasons were their legal status, customs and manners, as well as economic situation. The women, as the citizens of the country where, after the Industrial Revolution, the costs of living were the highest in Europe, could still afford to cover their expenses, and tried to find the alternative ways to lead their existence. Moreover, the Georgian and Victorian mores forced them into exile. The travels to the successively enlarged British Empire were easier for British women than for their counterparts in other nations. They could always find the help and care partly from the imperial administration in foreign countries. Due to this, they could easily cover the cost of living in these countries. Some of them contributed to the creation of the new profession based on traveling. Describing their adventures within the literary genre of travel writing, they developed the unique kind of women’s travel writing, which is now a part of world’s heritage. The pioneering enterprises in travel undertaken by British women underpin much of the travel and tourism culture, marking in turn the beginning of professional travel offices. Their travelogues expanded the knowledge of the British Empire as well as the world.